An Experimental Study On The Effect Of Disinfectant Sodium Hypochlorite (NaClo) Liquid On Density And Compressive Strength Concrete - Prilo Kurniawan; Agung, Sumarno, S.T., M.T. (Journal of World Conference (JWC), 2021)
The increasing use of disinfectants based on Sodium Hypochlorite (NaClO) for the need of preventive spraying for the COVID-19 pandemic, raises concerns about a decrease in strength in concrete structures. Therefore, the authors researched whether spraying disinfectants based on Sodium Hypochlorite (NaClO) would penetrate the density of the concrete, as well as ascertain whether the concrete structure might experience a massive decrease in compressive strength after spraying. The purpose of this study was to determine the effect of spraying and penetration of Sodium Hypochlorite (NaClO) disinfectant on the compressive strength of concrete. The method used in this research is experimental by doing a trial mix which being worked on at the Becakayu Toll Road Concrete Batching Plant Laboratory - PT. Waskita Beton Precast, Tbk. From the results of the research, the quality of K-500 concrete samples decreased in density by 0.74% in the NaClO-S treatment at the age of 7 days, 0.92% in the NaClO-R treatment at the age of 7 days, 1.09% in the NaClO-S treatment at the age of 14 days, 1.28% in the NaClO-R treatment at the age of 14 days, 1.61% in the NaClO-S treatment at the age of 28 days, 1.55% in the NaClO-R treatment at the age of 28 days. A Comparison of the compressive strength of NaClO-R treatment with Air-R treatment on K-500 quality concrete samples at the age of 7, 14, and 28 days sequentially was 13%, 27%, and 15% higher in the Air-S treatment. The biggest difference in the compressive strength value occurred in the k-500 quality concrete sample at the age of 14 days, namely 352.61 Kg / Cm2 for NaClo-S treatment versus 482.73 Kg / Cm2 for Water-S treatment.